Perception of the impact of traumatic events on Portuguese firefighters and attentional bias - Rodrigues, Fabiana Raquel Oliveira (2022)
Firefighters frequently participate in emergency situations and are exposed to stressful and potential trauma situations compared to the general population. Fires are part of what firefighters do, and the 2017 and 2018 fires were particularly intense and devastating in Portugal. In this context, the main objectives of this work were: (i) to explore the relationships between various relevant psychosocial variables in this context (trauma, distress, empathy, alexithymia, compassion fatigue (CF) and quality of life (QoL)) in Portuguese firefighters, focusing on trauma related to forest fires, and comparing with the general population; and (ii) explore the influence of attention processes among firefighters with low trauma, those with high trauma and the general population and the relationship with psychosocial variables. This work included a review study of empathy in emergency professionals, a validation study of a measure to assess HR, and three empirical cross-sectional studies. Participants were recruited from different fire brigades and cultural and recreational associations. The data suggest that firefighters have higher levels of exposure to traumatic events, feel more empathy and have less alexithymia than the general population, suggesting that emotional vulnerability, empathy and alexithymia are distinctive features and can be considered vulnerability factors for the development of symptoms related to traumatic stress among firefighters. In addition, higher levels of trauma in firefighters are associated with increased CF, and consequently, worse QoL, as we found evidence that, in addition to a direct positive effect of trauma on QoL, CF plays a partially mediating role in the relationship between trauma and QoL. Additionally, the results of a dotprobe task, which aimed to study possible attentional biases towards emotionally significant stimuli, allowed to give some support to the hypothesis that there is a greater attention bias towards clues related to fire in firefighters (although the difference between groups was not statistically significant). This bias was positively associated with the anxiety and personal discomfort reported by firefighters. The results of this work suggest the need to provide therapeutic interventions and strategies for the prevention and management of trauma and to minimize the psychological consequences of the firefighter's work, as well as developing programs aimed at attentional flexibility and self-regulation.